Techno-economic analysis of LVDC power distribution systems - Tan, Jonathan Keng Kiat (2014)
Today’s electric grid is mostly based on alternating current (AC), as well as the loads. However, recently there has been significant increase in direct current (DC) loads, especially in the low voltage (LV: <1kV). For example, the data centers, devices like laptop, PC, smart phone, TV, LED lighting, etc. These require AC-DC converters, causing great amount of power losses, due to the AC reactive power losses, and the converter losses. This final-year project (FYP) is aimed at determining the actual losses and their value, identify research required to advance the state of the art and make preliminary recommendations on how DC would be utilized at LV level, especially in the home in future.